2013
DOI: 10.1371/journal.pone.0075767
|View full text |Cite
|
Sign up to set email alerts
|

Conserving Biodiversity in a Human-Dominated World: Degradation of Marine Sessile Communities within a Protected Area with Conflicting Human Uses

Abstract: Conservation research aims at understanding whether present protection schemes are adequate for the maintenance of ecosystems structure and function across time. We evaluated long-term variation in rocky reef communities by comparing sites surveyed in 1993 and again in 2008. This research took place in Tigullio Gulf, an emblematic case study where various conservation measures, including a marine protected area, have been implemented to manage multiple human uses. Contrary to our prediction that protection sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 45 publications
2
62
0
Order By: Relevance
“…Based on the observed stressors trend and the scanty recent ecological literature on the area (Pancucci-Papadopoulou et al, 2012), the regime shift has probably occurred somewhere in the 1990s, similarly to what happened in other Mediterranean regions (Parravicini et al, 2013). Comparing only two points in time (1981 vs. 2013), might not be enough to assess whether a parallel change has occurred in biotic community.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Based on the observed stressors trend and the scanty recent ecological literature on the area (Pancucci-Papadopoulou et al, 2012), the regime shift has probably occurred somewhere in the 1990s, similarly to what happened in other Mediterranean regions (Parravicini et al, 2013). Comparing only two points in time (1981 vs. 2013), might not be enough to assess whether a parallel change has occurred in biotic community.…”
Section: Discussionmentioning
confidence: 97%
“…Yet, most research on Mediterranean marine ecosystems has traditionally been directed toward identification and classification purposes, as if they were stable units (Bianchi, 1997). On the contrary, recent research has shown that these alleged stable units have been undergoing rapid alteration in the last decades (Roghi et al, 2010;Parravicini et al, 2013). Bianchi & Morri (1983a, b) provided a first description of the coastal marine habitats of the Island of Kos (Greece, SE Aegean) on the basis of field work done in 1981, when tourism and coastal development were still in an early phase and sea water warming was not perceived yet.…”
Section: Introductionmentioning
confidence: 99%
“…These patterns confirm the sensitivity of coralligenous assemblages to human pressure (Balata et al 2007b, Piazzi et al 2012, Gatti et al 2015b, highlighting the suitability of these assemblages to be used as ecological indicators in monitoring survey and impact evaluation studies (Deter et al 2012, Sartoretto et al 2014, Gatti et al 2015a. Also, local protection might be not enough to prevent impacts on the structure and the ecological quality of coralligenous assemblages, as many organisms are more sensitive to large-scale alterations of water quality than to local disturbances (Parravicini et al 2013). Changes in macroalga abundance and composition among the studied environmental conditions were in agreement with patterns widely described (Piazzi et al 2012 and references therein).…”
Section: Discussionmentioning
confidence: 56%
“…Thus, depending on which of the two components is dominant in a coralligenous assemblages, the two individual indices considering only animals (ESCA-A) or only algae (ESCA) can be used accordingly and then also compared to understand which of the two components has been mostly affected. On the other hand, the concurrent use of the two components in the integrated ESCA-TA index can be effective in all the most common situations of high biodiverse coralligenous assemblages, as well as in situations where periodical fluctuations between animal-dominated and algal-dominated assemblages occur due to synergistic effects of local and global impacts (Parravicini et al 2013, Gatti et al 2015b). The results of this paper also showed that, although both the ESCA and ESCA-A indices, when used alone, clearly separated the highly urbanized locations from the other ones, the ESCA-TA index detected more finely the three environmental conditions, also revealing those subtle differences between locations under a regime of protection and locations affected by low levels of urbanization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation